Associação entre antígenos leucocitários humanos de classe II e a hepatite C crônica - Luiz Otavio Freire Cangussu (2008)
Background/Aims: The influence of immunogenetic factors to initiate or regulate the immune response in chronic hepatitis C has been explored recently. Human leucocyte antigen (HLA) is a crucial genetic factor related to susceptibility to HCV infection and progression of HCV liver injury. Hence, the aim of this study was to investigate the relationship of class II alleles HLA-DRB1 and DQB1 in patients with chronic hepatitis C.Methods: Ninety-nine white patients with confirmed chronic hepatitis C (anti-HCV and HCV RNA tests positive) were included: 48/99 (48.5%) were male, mean age of 51.5 ± 12 anos, and mean time of HCV infection of 22.2 ± 9.3 years. Liver fibrosis, scored by METAVIR, was categorized as severe fibrosis/cirrhosis (METAVIR F3-4) or without cirrhosis (METAVIR F0-2). 49/99 (49.5%) patients were cirrhotic. Patients were matched with 103 uninfected historical controls of general population of São Paulo (Brazil) (Morgun et al., 2004) and their class II allele fenotipic frequencies (Ff) were compared. HLA-DRB1*11, HLA-DRB1 (DRB1*1-16) e HLA-DQB1* alleles were determined by PCR-SSP in both groups.Results: The Ff of HLA-DRB1*11 were 11/99 (11.1%) and 22/103 (21.4%) in patients and controls (p=0.037 OR=0.46 IC95% 0.000.95). The Ff did not differ among patients with advanced fibrosis/cirrhosis (n=6/49, Ff:12.2%) and without cirrhosis (n=5/50, Ff:10,0%) (p=0.76). When the Ff of alleles DRB1*1101 and DRB1*1104 were compared between patients and controls, a lower Ff was noted in patients, but without statistical significance (DRB1*1101= 7/99 [7.1%] vs 13/103 [12.6%]) and DRB1*1104= (4/99 [4%] vs 8/103 [7.8%] in patients and controls, respectively) (p=0.24 e p=0.37). In an extended analysis, the results highlighted an increased phenotypic frequency of HLA-DQB1*0501 allele in patients with chronic hepatitis C compared to controls (34.4% and 20.4%, p=0.04 OR=2.04 CI95% 1.03-4.09), especially when non-cirrhotic group was compared to severe fibrosis/cirrhosis group (43.8% and 25.0%, p=0.04 OR=0.43, CI95% 0.00-0.97). The multivariate analysisrevealed that the age at biopsy and the presence of the allele HLA-DQB1*0501 were independent variables associated with severe fibrosis/cirrhosis (p=0.002 OR=1.06 IC 95% 1.02-1.11 and p=0.026 OR=0.34 IC95% 0.13-0.88). Conclusions: HLA-DRB1 alelle might play a role in the protective mechanisms against HCV infection, in particular the HLA-DRB1*11 specificity. Although a higher frequency of HLA-DQB1*0501 represent a predisposing factor to chronic hepatitis C,it may also confers lower risk of developing more severe liver fibrosis. Our extended HLA analysis corroborates the influence of immunogenetic factors influencing the clinical course of chronic hepatitis C.